KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS USE OF ANALGESICS AMONG PATIENTS IN RUBAGA HOSPITAL IN KAMPALA. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - FENI, DANIEL; Niwagira , Mulodokayi (Student's Journal of Health Research Africa, 2023)
Background: The study assessed the knowledge, attitude and practices towards the use of analgesics among the patients attending to hospital in Kampala Uganda. Methodology: The study employed was a descriptive cross-sectional in nature, on a sample of 50 respondents using simple random sampling technique. Semi-structured questionnaires were designed and used as data collection tool, data was using Microsoft to generate tables, pie charts and bar graphs for easy presentation of findings. Results: majority of the respondents (70%) understood analgesics as drugs that relieve and treat pain incidences, 66% of the respondents agreed that analgesics reduce pain in every pain incidences, 90% of the respondents have heard about analgesics as drugs of relieving and treating pain, 56% of the respondents obtained this information from the media and 45% obtained from their friends and family members and 30% obtained from the health workers, 76% of the respondents agreed that taking analgesics to relieve pain has side effects such as dizziness, headache, depression, 86% of the respondent recommended their friends and family members to get advice from health workers before utilizing over the counter medicines, 86% of the respondents agreed that they have used analgesics without consultation of the health workers. Conclusion: Patients had good attitude towards the use of analgesics for pain relieve and treatment but, most of them did not have more knowledge about the use of analgesics for treatment and relieving of pain. Recommendation: The ministry of health should carry out sensitization sessions to educate the patients about the possible side effects of analgesics and dangers of its use without consultation of the health workers in order to reduce or possibly eliminate the side effects of the drugs and resistances where necessary.